1999
DOI: 10.1177/153944929901900201
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Rater Reliability of a Home Fall Hazards Assessment Tool

Abstract: This study documents further development ofan environmental tool available to occupational therapists that has specifically been designed to identify home fall hazards. AbstractThe Westmead Home Safety Assessment provides an extensive list of potential hazards and wasdeveloped asa tool for occupational therapists to identify environmental hazards in the homes of persons who are at risk of falling. It was refined by procedures to establish content validity and by compiling an accompanying manual. Thus, the tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
3
29
0
1
Order By: Relevance
“…The addition of environmental modifications to a fall-risk prevention strategy can be effective (Lundebjerg et al, 2001). Tools such as the Westmead Home Safety Assessment (WeHSA) (L Clemson, Fitzgerald, & Heard, 1999a, 1999b), a very comprehensive tool that focuses on risks related to falls in traffic ways, indoors, living area, seating, bedroom, bathroom, kitchen and laundry, and on footwear, and medication management can be applied to older adults (L Clemson et al, 1999a, 1999b). A study that enrolled 391 visually impaired older adults for a year-long intervention found that WeHSA was successful in reducing falls.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of environmental modifications to a fall-risk prevention strategy can be effective (Lundebjerg et al, 2001). Tools such as the Westmead Home Safety Assessment (WeHSA) (L Clemson, Fitzgerald, & Heard, 1999a, 1999b), a very comprehensive tool that focuses on risks related to falls in traffic ways, indoors, living area, seating, bedroom, bathroom, kitchen and laundry, and on footwear, and medication management can be applied to older adults (L Clemson et al, 1999a, 1999b). A study that enrolled 391 visually impaired older adults for a year-long intervention found that WeHSA was successful in reducing falls.…”
Section: Discussionmentioning
confidence: 99%
“…Content and face validity testing and analysis of results 7: Reliability procedures (stability, equivalence and internal consistency) and analysis of data (Asher, 1996;Clemson et al, 1999). Consequently, this significant correlation of .962 demonstrated that CRAS scores had high level of agreement.…”
Section: Reliability Analysis: Stabilitymentioning
confidence: 96%
“…Als Vorbereitung der Machbarkeitsstudie für Wohnraumanpassungen ist zunächst eine Manualisierung der Intervention anzustreben und zudem sind die entsprechenden Instrumente für den deutschen Versorgungskontext zu validieren. Hierbei handelt es sich um folgende Instrumente: "The Westmead Home Safety Assessment (WeHSA)" (Clemson, 1997;Clemson, Fitzgerald, & Heard, 1999), "The home and community environment (HACE) instrument" (Keysor, Jette, & Haley, 2005), "The Falls Efficacy Scale International scale (FESI)" (Yardley, Beyer, Hauer, Kempen, Piot-Ziegler, & Todd, 2005), "The Reintegration to Normal Living Index (RNLI)" (Tooth, McKenna, Smith, & O'Rourke, 2003) and "The Nottingham Extended Activities of Daily Living scale (NEADL)" (Nouri, & Lincoln, 1987). Mit Blick auf die körperlichen Trainingsprogramme liegt bereits ein Manual im Originalkontext vor (Clemson, Munro, & Fiatarone Singh, 2014), welches für die Anwendbar-und Durchführbarkeit zu prüfen ist.…”
Section: Evidenzlageunclassified